Determinants of Cryptocurrency Adoption: The Role of AI, Financial Literacy, and Technological Awareness - Ninik Churniawati; Renita Selviana; Muhammad Mashudi Azrullah (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aimed to analyze the influence of technological awareness, financial literacy, Artificial Intelligence (AI), and personal innovation on the intention of the millennial generation in Pasuruan Regency to adopt cryptocurrencies and to explain the role of these factors in driving the acceptance of new technologies. Methodology: The research method involved 371,975 millennials in Pasuruan Regency, with a sampling technique using the Slovin formula with a margin of error of 5%. Data analysis was carried out using the Partial Least Squares (PLS) approach using WarpPLS 8.0 software. Results: The results of the study show that technological awareness, AI, and personal innovation have an impact on spirit is significant for behavioral intentions, while financial literacy has no direct influence on intentions but is proven to be significant for personal innovation. Conclusions: Technology awareness is a dominant factor in shaping crypto adoption intentions, both directly and through AI, whereas personal innovation strengthens the relationship. Limitations: This study focused solely on millennials in Pasuruan Regency. The variables used were limited to technological awareness, financial literacy, AI, and personal innovation. Other external factors, such as government regulations, market conditions, and individual psychological aspects, have not been investigated. Contributions: This research contributes theoretically by expanding the understanding of the influence of psychological factors, financial literacy, and digital technology on cryptocurrency adoption, and practically provides recommendations to accelerate adoption among the millennial generation by strengthening literacy, technological awareness, and optimizing AI to encourage smart, safe, and sustainable investment decisions.